استخدام الأرشیفات الوطنیة لشبکة الفیسبوک فى التنمیة المستدامة - د. نرمین ابراهیم على اللبان (المجلة الدولية لعلوم المكتبات والمعلومات)
This study dealt with the use of the Facebook in the field of sustainabledevelopment by the national archives. The study relied on the descriptiveapproach to analyze the national archives posts on the Facebook. The studysuggested the policy for using the social networks in promoting the sustainabledevelopment goals which were adopted by the national archives. It alsorecommended establishing an incorporated social network of sustainabledevelopment including all the national archives .